Blood pressure and particulate air pollution in schoolchildren of Lahore, Pakistan - Sughis Muhammad; Nawrot Tim S; Ihsan-; Amjad Asad; Nemery Benoit (BMC, 2012)
Abstract Background Air pollution is a growing health problem for urban populations in emerging economies. The present study examines the (cross-sectional) relation between blood pressure and particulate air pollution in schoolchildren of Lahore (Pakistan). Methods We recruited a sample of 8-12 year-old children (mean age 9.9 years; 45% girls) from two schools in Lahore situated in areas with low (n = 79) and high (n = 100) air pollution, respectively. During the study period (January-April 2009) particulate pollution [PM10 and PM2.5i.e. particles with aerodynamic diameters below 10 μm or 2.5 μm, respectively] was measured at the school sites with a laser operated device (Metone Aerocet 531). Blood pressure was measured, after 5 minutes of sitting rest, using an automated device (average of 5 consecutive measurements). Spot urine samples were also collected and concentrations of Na and K were measured. Results Mean daily values of PM2.5 were 28.5 μg/m3 (SD: 10.3) and 183 μg/m3 (SD: 30.2), in the low and high pollution areas, respectively. Systolic and diastolic blood pressure were significantly higher in children living in the high pollution area (115.9/70.9 mm Hg) than in the low pollution area (108.3/66.4 mm Hg), independently of age, gender, height, weight, socio-economic status, passive smoking and the urinary concentrations of Na, K, and creatinine. Conclusions In 8-12 year-old children, exposure to (traffic-related) air pollution was associated with higher systolic and diastolic blood pressure. These findings, if they persist, might have clinical relevance at older age.